Subunit Vaccine Delivery - Foged, Camilla; Rades, Thomas; Perrie, Yvonne; Hook, Sarah; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
This comprehensive volume compiles the concepts essential for the understanding of the pharmaceutical science and technology associated with the delivery of subunit vaccines. Twenty-one chapters are divided into four main parts: (I) Background; (2) Delivery Systems for Subunit Vaccines; (3) Delivery Routes, Devices and Dosage Forms; and (4) Pharmaceutical Analysis and Quality Control of Vaccines. Part one provide a basic background with respect to immunology and general vaccine classification. In part two, it presents representative types of vaccine delivery systems individually with focus on the physicochemical properties of the systems and their significance for the immune response they stimulate. These delivery systems include aluminum adjuvants, emulsions, liposomes, bilosomes, cubosomes/hexosomes, ISCOMs, virus-like particles, polymeric nano- and microparticles, gels, implants and cell-based delivery systems.   Following these chapters, part three addresses the challenges associated with vaccine delivery via specific routes of administration—in particular subcutaneous, intramuscular, oral, nasal, pulmonary, transdermal and vaginal administration. Furthermore, the specific administration routes are discussed in combination with device technologies relevant for the respective routes as well as dosage forms appropriate for the device technology. Finally, the fourth part concerns pharmaceutical analysis and quality control of subunit vaccines.
1 Immunological Background -- 2 Classification of Vaccines -- 3 Aluminum Adjuvants - Basic Concepts and Progress in Understanding -- 4 Emulsions as Vaccine Adjuvants -- 5 The application of liposomes as vaccine adjuvants -- 6 Developing Bilayer-based Delivery Systems for Oral Delivery of Subunit Vaccines -- 7 Cubosomes – Structure, Preparation and Use as an Antigen Delivery System -- 8 ISCOMs as a Vaccine Delivery System -- 9 Virus-like Particles, a Versatile Subunit Vaccine Platform -- 10 Polymeric Particulates for Subunit Vaccine Delivery -- 11 Gels as Vaccine Delivery Systems -- 12 Implants as Sustained Release Delivery Devices for Vaccine Antigens -- 13 Dendritic Cell-based Vaccines -- 14 Parenteral Vaccine Administration – Tried and True -- 15 Nasal Administration of Vaccines -- 16 Pulmonary Administration of Subunit Vaccines -- 17 Vaginal Delivery of Subunit Vaccines -- 18 Transcutaneous Administration -- 19 Pharmaceutical Analysis and Quality Control of Vaccines -- 20 The Physical Analysis of Vaccines -- 21 Characterizing the Association between Antigens and Adjuvants.
Keywords: Pharmaceutical technology; Vaccines; Medicine; Pharmaceutical Sciences/Technology.; Vaccine; Biomedicine, general